Teknik dan Instrumen Asesmen PAUD Ranah Afektif: Teknik Non Tes - Nurjanah, Efi (At- Ta'lim : Jurnal Pendidikan, 2017)
Achievement of child development can be known through appraisal or assessment. Assessment is gathering information to determine the quality and quantity of learners. In the assessment of possible collection of information on various matters related to the achievement of learners through various forms of assessment of both the test and non test. Assessment should be viewed as one of the important factors that determine the success of the process and learning outcomes. Assessment should be able to provide information to teachers to improve their teaching abilities and help learners achieve optimal learning progress.